The Influence of Loan Repayment and Scholarship Programs on Healthcare Provider Retention in Underserved Kansas - Locke, Erin; Dong, Frank; Stiles, Robert; Kellerman, Rick; Ablah, Elizabeth (Kansas Journal of Medicine, 2019)
Background. In an effort to redistribute healthcare providersto underserved areas, many states have turned to financialincentive programs. Despite substantial research on theseprograms on a national scale, little is known about the successof such programs in Kansas. The purpose of this studywas to provide insight into the relationship between financial incentive programs and provider retention in Kansas.Methods. A cross-sectional telephone survey was conducted inApril and May of 2011 with participants who had completedtheir obligations to the Kansas State Loan Repayment Program(SLRP), the National Health Service Corps (NHSC) Loan Repaymentprogram, or the National Health Service Corps Scholar shipprogram in Kansas between January 2006 and January 2011.Results. Of the 112 providers included in the study, 54.4% (n = 61)had left their program sites sometime after finishing their commitment,with the mean length of stay after the obligation periodended being 7.3 (median = 3) months. Of the 54 participants whohad left their program sites and whose current locations wereknown, 33.3% (n = 18) were located in new Health ProfessionalShortage Areas (HPSA), 25.9% (n = 14) were in a new non-HPSA,and 40.7% (n = 22) had left the state. Family satisfaction with thecommunity and attending a professional school in Kansas wereassociated statistically with retention of physicians in Kansas.Conclusions. Nearly half of all participants had remained attheir sites even after their obligation period ended, with familysatisfaction with the community appearing to be the strongestpredictor for retention among those who had stayed.Efforts to match a provider’s family with the community successfullyand to support the family through networking mayimprove future provider retention. KS J Med 2016;9(1):6-11.